PEMANFAATAN ABU SEKAM PADI SEBAGAI BAHAN PENGGANTI WATER GLASS DALAM PEMBUATAN MORTAR GEOPOLIMER CAMPURAN KERING - Firdaus, Firdaus; Matasya Putri, Gita (Ensiklopedia of Journal, 2024)
Oncrete is one of the most well-known building materials used in the construction of roads, bridges, buildings, dams, side channels, culverts, foundations and others. The development of concrete construction is carried out through the development of concrete using geopolymer concrete which is environmentally friendly and efficient in terms of energy utilization and shows that geopolymer concrete has technical properties, such as high strength and durability from the results of research that has been carried out. so far.Geopolymer is a concrete mixture in which the use of Portland cement as a binding paste is replaced with other materials such as fly ash or fly ash left over from burning coal. Geopolymer is an environmentally friendly material that was developed as an alternative to cement concrete.Keywords: Geopolymer Cement, Fly Ash, Rice Husk Ash, Dry Mix Mortar